2014
DOI: 10.1186/1479-5876-12-117
|View full text |Cite
|
Sign up to set email alerts
|

Discrepant alterations in main candidate genes among multiple primary melanomas

Abstract: BackgroundAlterations in key-regulator genes of disease pathogenesis (BRAF, cKIT, CyclinD1) have been evaluated in patients with multiple primary melanoma (MPM).MethodsOne hundred twelve MPM patients (96 cases with two primary melanomas, 15 with three, and 1 with four) were included into the study. Paired synchronous/asynchronous MPM tissues (N = 229) were analyzed for BRAF mutations and cKIT/CyclynD1 gene amplifications.ResultsBRAF mutations were identified in 109/229 (48%) primary melanomas, whereas cKIT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 45 publications
6
23
0
Order By: Relevance
“…9 The overall frequency of BRAF mutations found in our sample (41.2%) was in line with two large series of melanomas 29,30 and with other Italian cohorts. 16,17,23,31 Similarly, the prevalence rate of the different BRAF V600E and BRAF V600K mutations was consistent with that previously reported. 9 Concerning clinical characteristics, our results confirm that BRAF-mutated melanomas are associated with younger age and frequently occur on the trunk.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…9 The overall frequency of BRAF mutations found in our sample (41.2%) was in line with two large series of melanomas 29,30 and with other Italian cohorts. 16,17,23,31 Similarly, the prevalence rate of the different BRAF V600E and BRAF V600K mutations was consistent with that previously reported. 9 Concerning clinical characteristics, our results confirm that BRAF-mutated melanomas are associated with younger age and frequently occur on the trunk.…”
Section: Discussionsupporting
confidence: 91%
“…22 To date, only two studies investigated the somatic heterogeneity of multiple melanomas within the same patient, evaluating alterations in main candidate genes by molecular methods. 23,24 However, neither of the two analyzed the possible influence of germline mutations on the somatic diversity of MPM.…”
mentioning
confidence: 99%
“…The median tumor thickness of the index CMM in MPM‐patients in our study was thicker compared to patients with SPMs, which has previously been reported . These differences may imply a propensity among MPM‐patients to develop more aggressive disease and could reflect a clustering of fatal CMMs with specific genetic aberrations . However, more advanced T‐class in MPM‐patients could not explain the worse outcome in the present study, i.e ., the HRs were not affected after adjusting for stage and tumor thickness.…”
Section: Discussionsupporting
confidence: 53%
“…As 45% of cutaneous malignant melanomas are found to be BRAF mutated [6], at least half the melanomas of our patient were expected to be of wild type. Previous studies, in which MPM from a single sporadic patient were analyzed for the presence of BRAF mutations, have often yielded discordant results from differing lesions [18,19]. Conversely, two recent studies have reported identical somatic mutation status in three out of four and four out of six familial MPM cases with CDK4 and CDKN2A germline mutations, respectively [8,9].…”
Section: Discussionmentioning
confidence: 99%